Investigation of the fracture behaviors of windshield laminated glass used in high-speed trains. (1st January 2019) - Peng, Yong; Ma, Wen; Wang, Shiming; Wang, Kui; Gao, Guangjun
Abstract: The objective of this study is to investigate the fracture behaviors of windshield laminated glass for high-speed trains. For this purpose, tempered glass specimens sampled from constituent components of polyvinyl butyral (PVB) laminated windshield panes were tested using the following tests: flexural strength test, quasi-static uniaxial tensile test, low strain rate compression test and dynamic compressive test with split Hopkinson pressure bar (SHPB). Together with simulations, the testing results were used to determine the constitutive constants of the Johnson-Holmquist ceramic (JHC) model, including the equation of state, the strength criterion and the strain-rate effect. To validate the JHC model, it is used to simulate a safety hammer impact test on PVB-Laminated tempered glass (PVB-LTG). The simulation results showed that the JHC model with tempered material constants for PVB-LTG successfully predicted the impact response of windshields. The practical implications of fragmentation and cracking are also discussed.